The Development of Rubber Compound based on Natural Rubber (NR) and Ethylene-Propylene-Diene-Monomer (EPDM) Rubber for Playground Rubber Mat - Bussaya Rattanasupa; Wirunya Keawwattana (Agriculture and Natural Resources, 2007)
The development of rubber compound for playground rubber mat by studying the effect of light-colored fillers on cure characteristics, mechanical properties of natural rubber (NR) and ethylene propylene diene monomer (EPDM) rubber blend was investigated. It was found that at the same filler loading (100 phr), CaCO3 filled-rubber showed the lowest cure time (tc90) and also the best mechanical properties compared with other fillers. At various filler loading (50, 100 and 150 phr), rubbers filled with CaCO3 and natural zeolite at 150 phr both showed the lowest cure time and highest hardness, but CaCO3 displayed the lowest values of tensile strength and elongation at break. In addition, the influence of the vulcanization system (conventional vulcanization (CV), semi-efficient vulcanization (semi-EV), and efficient vulcanization (EV)) on the mechanical properties of the 100 phr CaCO3 filled vulcanizates were investigated and discovered that the CV system showed the highest mechanical properties.